ABO blood type correlates with survival in hepatocellular carcinoma following hepatectomy - Tao Wu (Nature Portfolio, 2017)
Abstract ABO blood types are associated with the prognosis of several malignancies. However, the role of the ABO blood type in hepatocellular carcinoma (HCC) remains elusive. Here, we evaluated the prognostic role of the ABO blood group in 691 HCC patients after hepatectomy by Cox regression analysis. A prognostic nomogram was generated to predict the 3 and 5-year overall survival (OS). A total of 262 HCC patients (37.9%) had blood group O, 199 (28.8%) had blood group A, 165 (23.9%) had blood group B, and 65 (9.4%) had blood group AB. The median OS was 55 months in patients with blood group O, 39 months for blood group A, 34 months for blood group B, and 34 months for blood group AB patients (P = 0.001, log-rank test). There were significant differences in OS between patients with blood groups O and A [hazard ratio (HR) = 1.416; 95% CI, 1.101–1.820; P = 0.007], blood group B (HR = 1.736; 95% CI, 1.333–2.262; P < 0.001), blood group AB (HR = 1.739; 95% CI, 1.210–2.499; P = 0.003) and non-O blood groups (HR = 1.485; 95% CI, 1.204–1.830; P < 0.001). Our constructed nomogram (c-index = 0.687) predicted the prognosis more accurately than the TNM stage alone(c-index = 0.601). In conclusion, non-O blood groups are poor prognostic indicators for HCC following hepatectomy. Our findings justify further external validation in larger cohorts.